Risk factors and antibiotic sensitivity of aerobic bacteria in Chinese children with adenoid hypertrophy - Lujie Zuo; Li He; Aiping Huang; Yingying Liu; Aiying Zhang; Li Wang; Yingluan Song; Jiangqiao Geng (BMC, 2022)
Abstract Background Bacterial infection of adenoid is currently considered to be an important cause of adenoid hypertrophy (AH) in children. Although several bacteriology studies on adenoid diseases have been reported, the aerobic bacterial study regarding risk factors and antibiotic sensitivity of AH in Chinese children is lacking. This study aims to investigate the risk factors for aerobic bacterial colonization of AH in Chinese children and to elucidate aerobic bacterial profiles and antibiotic sensitivity. Methods Samples were collected from the adenoid core and surface tissue of 466 children undergoing adenoidectomy. Aerobic cultures and antibiotic sensitivity were observed. The risk factors for bacterial colonization of adenoid were analyzed statistically. Results A total of 143 children could be detected opportunistic pathogens in adenoid surface and/or core tissue, with a carriage rate of 30.7%. The presence of chronic rhinosinusitis, tonsillar hypertrophy and adenoidal size were the risk factors for aerobic bacterial colonization of adenoid in univariate analysis. Multivariate analysis showed that chronic rhinosinusitis and tonsil hypertrophy were significant variables associated with the aerobic bacterial colonization. The most frequently isolated aerobic bacteria were Haemophilus influenzae, followed by Staphylococcus aureus and Streptococcus pneumoniae. There was no statistically significant difference in bacterial species between the adenoid surface and core. The above common bacteria were more sensitive to cephalosporins and quinolones antibiotics, and significantly resistant to penicillin antibiotics and non-β-lactamase inhibitors. Conclusion Our results provide recent aerobic bacterial profiles for AH among Chinese children and confirm the risk factors and antibiotic sensitivity. This study contributes to understanding the role of different risk factors in the development of AH and will be helpful to the treatment of AH among Chinese children.